NOTES ON INDONESIAN FRESHWATER ALGAE - IV. Concerning Euastrum moebii (Borge) Scott & Prescott comb. nov. and Euastrum turgidum Wallich. - SCOTT, ARTHUR M.; PRESCOTT, GERALD W. (REINWARDTIA, 1960)
The desmid presently known as Mierasterias moebii (Borge) West & West is transferred back to the genus Euastrum where it was originally placed by its discoverer, together with its several varieties, for reasons that are discussed in detail. There are described one new variety, var. diplocanthylum from Australia, and one new forma, var. tetrachastriforme fa. latum from Borneo. New illustrations are given for Euastrum, turgidum Wall., and criteria are suggested for differentiating this plant from the closely similar E. moebii.